Pelabelan Harmonis Ganjil pada Graf Ular Jaring Berlipat - Fery Firmansah (Universitas PGRI Palembang, 2020)
Graphs that have odd harmonious labeling properties are called odd harmonious graphs. The purpose of this study to obtain a new graph class construction with its properties, but also to prove that the new graph class has odd harmonious labeling properties. The research method used consisted of several steps namely data research preparations, research investigations and verification of results. The results of this study, we will provide a construction of a new graph class, that is, the pleated net snake graph and its properties. Furthermore, it will be proven that the pleated net snake graph has odd harmonious labeling properties, so that the pleated net snake graph is an odd harmonious graph.